Methacholine-Induced Cough in the Absence of Asthma: Insights From Impulse Oscillometry - Sood, Nilita; Wasilewski, Nastasia V.; Day, Andrew G.; Wall, Taylar; Fisher, Thomas; Fisher, John T.; Lougheed, M. Diane (Frontiers in Physiology, 2020)
The pathophysiologic differences between methacholine-induced cough but normal airway sensitivity (COUGH) and healthy individuals (CONTROL) are incompletely understood and may be due to differences in the bronchodilating effect of deep inspirations (DIs). The purpose of this study is to compare the bronchodilating effect of DIs in individuals with classic asthma (CA), cough variant asthma (CVA), and COUGH with CONTROL and to assess impulse oscillometry (IOS) measures as predictors of the bronchodilating effect of DIs. Methods: 43 adults (18 female; 44.8 ± 12.3 years (Mean ± SD); n=11 CA, n=10 CVA, n=7 COUGH, n=15 CONTROL) underwent modified high-dose methacholine challenge, with IOS and partial/maximal expiratory flow volume maneuvers (PEFV/MEFV; used to calculate DI Index) to a maximum change (Δ) in FEV1 of 50% from baseline (MAX). Cough count and dyspnea were measured at each dose. The relation between spirometry, lung volume and IOS parameters and DI Index was assessed at baseline and MAX using linear regression analysis. Results: Cough frequency, dyspnea intensity and baseline peripheral resistance (R5-R20) were significantly greater in COUGH compared with CONTROL (p=0.006, p=0.029 and p=0.035 respectively). At MAX, the DI Index was significantly lower in COUGH (0.01 ± 0.36) compared with CA (0.67 ± 0.97, p=0.008), CVA (0.51 ± 0.73, p=0.012) and CONTROL (0.68 ± 0.45, p=0.005). R5-R20 and resonant frequency (Fres) were independent IOS predictors of the DI Index. Conclusion: The bronchodilating effect is impaired in COUGH and preserved in mild CA, CVA and CONTROL. Increased peripheral airway resistance and decreased resonant frequency are associated with a decreased DI Index. COUGH is a clinical phenotype distinct from healthy normals and asthma.